2015
DOI: 10.3402/meo.v20.25105
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between academic performance and recreation use among first-year medical students

Abstract: IntroductionSelf-care activities, including exercise, may be neglected by medical students in response to increasing academic demands. Low levels of exercise among medical students may have ripple effects on patient care and counseling. This study investigates the reciprocal role of recreation use and academic performance among first-year medical students.MethodsWe combined retrospective administrative data from four cohorts of first-year medical students at the University of Illinois at Urbana-Champaign from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
(23 reference statements)
0
22
0
2
Order By: Relevance
“…Slade and Kies recently communicated a similar positive correlation between engagement in sports-based EAs and higher academic performance in final examinations. 6 Lumley and colleagues 1 showed that the time spent on EAs had a very negligible deleterious influence on academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slade and Kies recently communicated a similar positive correlation between engagement in sports-based EAs and higher academic performance in final examinations. 6 Lumley and colleagues 1 showed that the time spent on EAs had a very negligible deleterious influence on academic performance.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Participation in research-related EAs has been linked to better academic performance and improved research-specific, higher-cognitive and transferable skills. 4 , 5 Likewise, participation in non-research-related EAs, such as sports 6 , 7 and service learning, 8 , 9 has been associated with a superior academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Undergraduate voluntary participation can positively affect educational outcomes such as the acquisition of higher degrees 23 . In fact, it was reported that students who reduce their recreation had, on average, lower examination results 24 . Lumley et al reported a diversity of extracurricular activities among final year medical students 25 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Slade et al have found that changes in recreation before an exam had a positive influence on exam performance. 12 There were few studies among medical students to assess the trends of physical activity and its influence on academic performance and physical and mental health. Hence the present study had been undertaken with an aim to study various trends of physical activity, health status and academic performance among medical students and to find out any association between physical activity and health status, academic performance of medical students.…”
Section: Introductionmentioning
confidence: 99%